Mickey Mouse sign in a case of polyostotic Paget’s disease - Goyal, Alpesh; Boro, Hiya (Indian Journal of Case Reports, 2017)
Paget’s disease of bone is an osseous dysplasia affecting the middle-aged and elderly population. It is most common in Northern Europe and Australia and is rare in Asia and Africa. We report a case of 50 year old menopausal female, who presented to us with features of polyostotic Paget’s disease of bone. The classical radiographic and bone scintigraphic findings of the patient have been described.